Inhibition of CRISPR-Cas9 ribonucleoprotein complex assembly by anti-CRISPR AcrIIC2 - Annoj Thavalingam (Nature Portfolio, 2019)
Anti-CRISPR proteins offer the means of regulating CRISPR-Cas9 activity. Here the authors present the structure and biochemical characterisation of AcrIIC2 Nme alone and in complex with Cas9.